Knowledge and Adaptation of Vegetable Farmers in Kerato Village, Unter Iwes District, Sumbawa in Facing the Phenomenon of Climate Change - Ieke Wulan Ayu; Ikhlas Suhada; Soemarno (Future Science)
The El Nino phenomenon due to the impact of climate change causes extreme drought and drought, resulting in damage and crop failure. Adaptive action and knowledge can prevent farmers from the impacts of climate change. The research objective was to determine the knowledge and adaptation of vegetable farmers in Kerato Village to climate change and the factors that affect farmers in adapting to climate change. The research was conducted in Kerato Village, Unter Iwes District, Sumbawa Regency, from April to July 2020, using qualitative methods. Data collected through structured interviews, focus group discussions (FGD) and observations. The results show that the knowledge of climate change which is owned by vegetable farmers in Kerato Village is still low. The adaptation made by vegetable farmers in Kerato Village to climate change, namely by shifting planting times, changing cropping patterns, changing irrigation and drainage techniques, changing soil cultivation techniques and changing pest control techniques. The conclusions of the research are: (1) All vegetable farmers in Kerato Village are aware of climate change, including: shifting seasons, low rainfall, and increasing temperature; (2) The pattern of adaptation carried out by Kerato Village vegetable farmers, includes: shifting planting time, changing cropping patterns, changing irrigation and drainage techniques, changing soil processing techniques and changing pest control techniques; (3) Factors that influence farmers' decision factors in adapting to their farming experience, level of education, skill ownership, participation in farmer groups and access to agricultural information. The research implications are: (1) The availability of information regarding the adaptation and knowledge of vegetable farmers to climate change; (2) Providing information on the adaptation capacity of vegetable farmers to climate change, which can be used as material for recommendations by policy makers on climate change adaptation and mitigation.